2018
DOI: 10.1016/s1470-2045(18)30362-0
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab and temozolomide in patients with first recurrence of WHO grade II and III glioma, without 1p/19q co-deletion (TAVAREC): a randomised controlled phase 2 EORTC trial

Abstract: Roche Pharmaceuticals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 24 publications
2
56
0
1
Order By: Relevance
“…The main chemotherapy used at relapse is temozolomide because of its good blood-brain barrier penetration and its favorable safety profile [ 119 , 120 ]. Bevacizumab, commonly used for recurrent high-grade astrocytomas, was evaluated in the “TAVAREC” randomized phase II trial in association with temozolomide, but no survival benefit was observed [ 121 ]. Regarding the other potential drugs for LGG at recurrence, the use of everolimus was associated with disease stability in a phase II trial [ 122 ], while the development of immunotherapies like vaccines [ 123 ] could open new opportunities for LGG patients.…”
Section: Role Of Chemotherapy and New Systemic Treatmentsmentioning
confidence: 99%
“…The main chemotherapy used at relapse is temozolomide because of its good blood-brain barrier penetration and its favorable safety profile [ 119 , 120 ]. Bevacizumab, commonly used for recurrent high-grade astrocytomas, was evaluated in the “TAVAREC” randomized phase II trial in association with temozolomide, but no survival benefit was observed [ 121 ]. Regarding the other potential drugs for LGG at recurrence, the use of everolimus was associated with disease stability in a phase II trial [ 122 ], while the development of immunotherapies like vaccines [ 123 ] could open new opportunities for LGG patients.…”
Section: Role Of Chemotherapy and New Systemic Treatmentsmentioning
confidence: 99%
“…Glioblastoma is the most common primary malignant brain tumor and continues to carry a very poor prognosis with a median survival of~20 months 1,2 Challenges in treating glioblastoma center around its molecular and cellular heterogeneity, including the presence of small populations of brain tumor initiating cells (BTICs) that are typically resistant to standard treatment regimens. 3,4 This complexity necessitates the development of therapies for targets that intersect multiple tumor-promoting pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Baumert et al, in recently published randomized study results, have reported that they did not find any significant difference in outcome of the overall patient population treated with either radiotherapy alone or TMZ chemotherapy alone [12]. On the other hand, in the just published EORTC trial, randomized controlled research on phase 2 published in Lancet, van den Bent et al have found no evidence of improved overall survival with bevacizumab (Avastin) and TMZ combination treatment versus TMZ monotherapy in patients with first recurrence of WHO grades II and III glioma, without 1p/19q codeletion [13].…”
Section: Where We Are Nowmentioning
confidence: 99%
“…Achieving a gross total resection of the tumor without significant complication requires a thorough understanding of available surgical approaches [15,17,[30][31][32]. For majority of those patients, short-course radiotherapy with concurrent and adjuvant TMZ will bring a benefit, while gain from bevacizumab is limited [13]. There have been some ideas that certain antiepileptics also have a favorable effect on the outcome with glioma patients, but these studies have not given affirmative results [33].…”
Section: Is There Hopementioning
confidence: 99%